Insomnia symptoms increase during pregnancy, but no increase in sleepiness - Associations with symptoms of depression and anxiety - Aukia Linda; Paavonen E Juulia; Jänkälä Tuire; Tolvanen Mimmi; Korja Riikka; Karlsson Linnea; Karlsson Hasse; Polo-Kantola Päivi (ELSEVIER, 2022)
Objective
To evaluate alteration in insomnia and sleepiness symptoms during pregnancy and assess early pregnancy risk factors for these symptoms, especially depressive and anxiety symptoms.
Methods
A cohort of 1858 women was enrolled from the FinnBrain Birth Cohort Study. Insomnia and sleepiness symptoms were measured in early, mid- and late pregnancy with the Basic Nordic Sleep Questionnaire. Depressive symptoms were measured using the Edinburgh Postnatal Depression Scale and anxiety symptoms with the Symptom Checklist-90/Anxiety Scale. General linear models for repeated measures were conducted.
Results
General sleep quality decreased (p < 0.001) and all insomnia types (p < 0.001) and sleep latencies (p < 0.001) increased as pregnancy proceeded. Snoring increased, but witnessed apneas remained rare. Nevertheless, morning (p = 0.019) and daytime (p < 0.001) sleepiness decreased from early to both mid-pregnancy and late pregnancy (p = 0.006 and p = 0.039). Women took more naps in early and late pregnancy compared to mid-pregnancy (both p < 0.001). Women with higher baseline anxiety symptoms had greater increase in sleep latency. At each pregnancy point, higher depressive and anxiety symptoms were associated with higher insomnia (p < 0.001) and sleepiness scores (p < 0.001) and higher depressive symptoms with longer sleep latencies (p < 0.001).
Conclusion
We found a marked increase in insomnia symptoms throughout pregnancy. However, sleepiness symptoms did not increase correspondingly. Both depressive and anxiety symptoms in early pregnancy were associated with higher insomnia and sleepiness symptoms in later stages of pregnancy which emphasizes the importance of their assessment in early pregnancy.